Susceptibility of Phlebotomus papatasi (Diptera: Psychodidae) against DDT and Deltamethrin in an Endemic Focus of Zoonotic Cutaneous Leishmaniasis in Iran - Amrollah Azarm; Hassan Vatandoost; Mona Koosha; Amir Ahmad Akhavan; Mehdi Mohebali; Zahra Saeidi; Awat Dehghan; Mohammad Ali Oshaghi (Tehran University of Medical Sciences, 2024)
Background: Phlebotomus papatasi (Diptera: Psychodidae) is the main vector of zoonotic cutaneous leishmaniasis (ZCL) in Iran. The nonstandard use of pesticides against pests, particularly in agriculture, indirectly has caused the development of resistance and, consequently, the threat of control measures in ZCL endemic areas. Up to 2023, several reports of resistance in Ph. papatasi have been declared in the old world. The purpose of this study was to measure the lethal time (LT50 and LT90) of Ph. papatasi sand flies in the ZCL endemic center of Esfahan to DDT and deltamethrin insecticides. Methods: Sand flies were collected in Borkhar and were tested using WHO adult mosquito test kit against DDT 4% and deltamethrin 0.0002%. The sand fly's survival was recorded during exposure time in 225, 450|, 900, 1800, and 3600-seconds' intervals for DDT and Deltamethrin and they were allowed to recover for 24 hours. Then LT50 and LT90 were analyzed using probit software. Phlebotomus papatasi were identified using morphological keys and other sand flies' species were excluded from the analysis. Results: The insecticide against female Ph. papatasi revealed hundred percent mortality when exposed to DDT 4% and deltamethrin 0.0002%. The LT50 and LT90 were 19.32 and 22.74 minutes for DDT 4% and 39.92 and 51.33 minutes for deltamethrin 0.0002% respectively. Conclusion: Results of this study revealed that Ph. papatasi is still susceptible to DDT and deltamethrin. This data provides valuable knowledge to implement effective control strategies against ZCL main vector and help to manage insecticide resistance in the region.